Social institutions politics and education - Harrison, Ken (Oakville : Magic Lantern Group)
Dicusses the function of social institutions in terms of meeting society's needs
Executive producer, Craig Mayes ; editor, Michael Coleman
Narrator: Lynn Mathis
Keywords: Sociology; Social institutions